solve question c, d, j
Attachments:
![](https://hi-static.z-dn.net/files/d59/7195feb79ecc99d31a89b06674ff91dc.jpg)
Answers
Answered by
0
(c) = (a²+b²)(-a²+b²)
= -a⁴+ a²b² - a²b² +(b²)²
= -a⁴+b⁴
(d) = (-a+c)(-a+c)
It can be written as
= (c-a)(c-a)
= (c-a)²
Using identity
(a-b)²= a²+b²- 2ab
= c²+a²-2ac
(j)
Using identity
(a+b)²= a²+b²+2ab
= (ab+cb)²-2ab²c
= (a²b²+c²b²+2ab²c)-2ab²c
= a²b²+ c²b²
Hope this helps you.....✌
= -a⁴+ a²b² - a²b² +(b²)²
= -a⁴+b⁴
(d) = (-a+c)(-a+c)
It can be written as
= (c-a)(c-a)
= (c-a)²
Using identity
(a-b)²= a²+b²- 2ab
= c²+a²-2ac
(j)
Using identity
(a+b)²= a²+b²+2ab
= (ab+cb)²-2ab²c
= (a²b²+c²b²+2ab²c)-2ab²c
= a²b²+ c²b²
Hope this helps you.....✌
Similar questions